RESPONSE TO THE PRODUCTION OF TWO VARIETIES OF OKRA PLANT (Abelmoschus esculentus L. Moench) DUE TO THE COMBINATION TREATMENT OF DRY ORGANIC FERTILIZER FROM COW MANURE AND LIQUID ORGANIC FERTILIZER FROM FRUITS WASTE - Taufiq, Muhammad; Ginting, Tri Yaninta (Proceeding International Conference Keputeraan Prof. H. Kadirun Yahya; Vol 1 No 1 (2022): 1st International Conference Keputeraan Prof. Kadirun Yahya, 2022)
The application of organic fertilizers in agricultural systems has many benefits in increasing soil fertility. The okra plant is a type of vegetable crop that has started to be widely consumed and can compete in the export market. The purpose of this study was to analyze the production and the interaction of two varieties of okra ( Abelmoschus esculentus L. Moench) due to the combined treatment of dry organic fertilizer from cow manure and liquid organic fertilizer from fruit waste. The research method used was a factorial randomized block design consisting of 2 factors. The first factor was the variety treatment which was divided into 2 levels, namely V1 = green okra of Lucky Five 473 F1 variety, and V2 = red okra of Zahira IPB variety. The second factor was the combination treatment of the application of dry organic fretilizer (DOF) from cow manure and liquid organic fertilizer (LOF) from fruit waste which was divided into 4 levels, namely P0 = 0.0 kg DOF + 0 ml LOF, P1 = 1.5 kg DOF + 50 ml LOF, P2 = 3.0 kg DOF + 50 ml LOF, P3 = 4.5 kg DOF + 50 ml LOF. Parameters observed were number of fruit per sample, number of fruit per plot, the weight of fruit per sample, and weight of fruit per plot. The results showed that the two types varieties of okra plant did affect the parameters of the number of fruits per sample, the number of fruits per plot, weight of fruits per sample, and weight of fruits per plot, where the best variety treatment was the green okra plants (V1). The combination treatment of the application of dry organic fertilizer (DOF) from cow manure with liquid organic fertilizer (LOF) from fruit waste did affect the parameters of the number of fruits per sample, the number of fruits per plot, weight of fruits per sample, and weight of fruits per plot, where the best treatment was P3 (4.5 kg DOF + 50 ml LOF).